The effect of educational intervention based on the theory of planned behavior on improving physical and nutrition status of obese and overweight women - Ali Khani Jeihooni; Mehdi Layeghiasl; Asiyeh Yari; Tayebeh Rakhshani (BMC, 2022)
Abstract Background Regarding the high rate of obesity and overweight among women, develop a comprehensive and effective program it seems necessary to improve their nutritional behaviors and physical activity. This study aims to survey the effect of educational intervention based on the theory of planned behavior (TPB) on improving physical and nutritional activities of obese and overweight women. Methods This experimental study was performed on 400 obese and overweight women over the age of 20. The sampling method was A simple random sampling. The data collection was valid and reliable self-reports measure, questionnaires. This tools was including demographic information, questionnaire based on the constructs of the theory of planned behavior, physical activity performance questionnaire and nutritional performance questionnaire that individuals completed before and 6 months after the educational intervention. The training intervention for the experimental group consisted of 12 sessions of 50-55 min. Data analyzed by SPSS22 and by using chi-square test, independent t-test and paired t-test. Results Findings showed that before the educational intervention, was no significant difference between the experimental and control groups in terms of education, household monthly income, occupation, mean age, marital status, awareness, attitude, perceived behavioral control, subjective norms, physical activity and nutritional behavioral intentions, and physical activity and nutritional performance, weight and BMI. However, six months after the training intervention, there was a significant increase in each of the TPB contracts, weight and BMI in the experimental group, while no significant difference was observed in the control group. The meaningful level was considered 0.05. Conclusion Our findings partially support of applying theory of planned behavior in reducing the weight, BMI and improved nutritional performance and physical activity of the study subjects. TPB could be an important strategy for effective future educational interventions.